FEATURES OF ELEMENTAL COMPOSITION IN SCHOOLCHILD WITH ASCARIASIS - I. A. Lokhmatova (LLC "Diagnostics and Vaccines", 2018)
Objective: to study the features of elemental composition in schoolchildren with ascariasis and to compare the revealed features with clinical manifestations of invasion.Materials and methods: 43 children (7 - 18 years) with ascariasis (diagnostics was carried out by the method of thick smear according to Kato two times with an interval of 3 days and the method of flotation according to Kalantaryan): I subgroup - children of primary school age - 15 people, II subgroup - children of senior school age - 28 people. The control group was 32 relatively healthy schoolchildren. It was determined of 19 chemical elements (Ca, Zn, K, I, Cu, Se, Fe, Mn, Cr, S, Br, Cl, Co, Ni, Mo, Sr, Ba, Pb, Cd) in children's hair was determined.Results: Low content of Zn, Cu, I, Se, Fe and Se, Br, Co, Ni, as well as increase of toxic Pb and Cd in the hair of junior schoolchildren with ascariasis is established. The invaders of high school students have a significantly lowered level of Ca, Zn, Cu, Fe and Br, Ni, Mo, as well as an elevated level of Ba, Pb, Cd.Conclusions: Imbalance of micro- and macroelements in the intestinal stage of ascariasis in children is an important pathogenetic link in the formation of the main clinical syndromes in children. Replenishment of microelement imbalance at the stage of treatment and rehabilitation of children with ascariasis is pathogenetically grounded and promotes the speedy restoration of all disturbed functions of the macroorganism.